2016
DOI: 10.1016/j.ijchp.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment, symptoms of depression, and health-related quality of life in patients with severe stable heart failure

Abstract: Background/Objective: Diseases of the cardiovascular system and depression are common, and they often coexist, significantly deteriorating the quality of life. Another factor influencing vital functions is impairment of cognitive functions occurring in patients with heart failure (HF). Deficits of different degrees of severity have been observed within a variety of cognitive domains. Cognitive deficits, which may impair daily functioning, hinder adaptation to the disease and worsen prognosis, are also observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
0
25
0
7
Order By: Relevance
“…The age range of the sample used in the present study introduces some important criteria due to the fact that the participants had autonomy to perform their daily activities. This criterion differs from other studies where the lack of autonomy was considered (Moryś, Pąchalska, Bellwon, & Gruchała, 2016). This study intended to evaluate a non-clinical sample and the strategy followed was to collect the sample within senior universities.…”
Section: Discussionmentioning
confidence: 79%
“…The age range of the sample used in the present study introduces some important criteria due to the fact that the participants had autonomy to perform their daily activities. This criterion differs from other studies where the lack of autonomy was considered (Moryś, Pąchalska, Bellwon, & Gruchała, 2016). This study intended to evaluate a non-clinical sample and the strategy followed was to collect the sample within senior universities.…”
Section: Discussionmentioning
confidence: 79%
“…This may be explained not only by the fact that a reduction of AHI implies less sleep fragmentation and, thus, higher sleep efficiency but also by the beneficial effect that a balanced diet and exercise have on general sleep quality . As sleep quality is related to daily functioning and mood, which have an impact on overall quality of life, lifestyle interventions may entail not only reductions of cognitive impairments and depressive symptoms but also an increase of the patients' overall well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we estimated the odds ratios (ORs) and 95% confidence intervals (CIs) of avoidance behaviors for the presence of depressive symptoms (BDI-II ≥ 14) using logistic regression models. Then, we sequentially introduced groups of variables into the model: first demographic and clinical variables and then avoidance behaviors, because these are known from previous studies to be associated with depressive symptoms ( Moryś et al, 2016 ). The independent variables included in this model were based on a priori clinical judgment and the existing literature, and included 1) age, 2) sex, 3) family structure (living alone vs. living with family), 4) employment status, 5) presence of heart failure, and 6) having experienced electric shock.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that depressive symptoms were a risk factor for poor adherence ( Luyster, Hughes, & Gunstad, 2009 ), arrhythmic episodes ( Tzeis et al, 2011 ), phantom shock ( Starrenburg, Kraaier, Pedersen, Scholten, & Van Der Palen, 2014 ), rehospitalization ( Shalaby, Brumberg, El-Saed, & Saba, 2012 ), and increased mortality rates ( van den Broek et al, 2013 , Whang et al, 2005 ). In contrast, some earlier studies suggested that depressive symptoms are predicted by being younger, being female, having poor social support (e.g., living alone), having a poor physical condition (e.g., presence of heart failure), and electric shock events among patients with ICDs ( Moryś, Pąchalska, Bellwon, & Gruchała, 2016 ). However, the personal factors that are related to depressive symptoms have not yet been fully defined, although factors related anxiety symptoms have been increasingly clarified ( Sears & Conti, 2002 ).…”
mentioning
confidence: 86%